Effect Prenatal Yoga on Pregnancy: Literatur Review - Susanti, Nurul Fatimah; Listya, Endah Purda; Octaliana, Hasrita (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Pregnancy is a process characterized by various physiological and psychological changes. Yoga has been shown to reduce discomfort due to physiological and psychological changes in pregnancy. The study was made to update and provide a comprehensive picture of the effects of prenatal yoga on pregnancy compared to standard prenatal care. This integrative literature review was based on databases namely Pubmed and ScienceDirect. Inclusion criteria were articles published in 2019-2024, written in English, and all articles were available and accessible. Only original articles and those with experimental designs were included.  From 1085 articles, six articles were reviewed. The quality of the selected articles was determined using the Olsen-Baisch Scoring tool. Yoga can reduce pregnancy discomfort related to the gastrointestinal and respiratory systems and improve sleep quality. Psychologically, yoga can help reduce stress, depression and anxiety and improve mental health. Yoga can reduce the incidence of Cesarean Section, reduce the occurrence of labor induction and reduce the incidence of under-term labor and reduce the perception of pain and fear of facing labor.